Enhancing the production of acetyl-triacylglycerols through metabolic engineering of the oilseed crop Camelina sativa - Alkotami, Linah (Kansas State University, 2018)
Many Euonymus species express an acetyltransferase enzyme in their seeds which catalyzes the transfer of an acetyl group from acetyl-CoA to the sn-3 position of diacylglycerol (DAG) producing unusual acetyl-1,2-diacyl-sn-glycerols (acetyl-TAG). The presence of the sn-3 acetate group gives acetyl-TAG with unique physical properties over regular triacylglycerol (TAG) found in vegetable oils. The useful characteristics of acetyl-TAG oil offer advantages for its use as emulsifiers, lubricants, and 'drop-in' biofuels. One enzyme, Euonymus alatus diacylglycerol acetyltransferase (EaDAcT), responsible for acetyl-TAG synthesis in nature was previously isolated from the seeds of Euonymus alatus (burning bush) and expressed in the oilseed crop Camelina sativa. Expression of EaDAcT successfully led to production of high levels of acetyl-TAG in camelina seeds. To further increase acetyl-TAG accumulation in transgenic camelina seeds, multiple strategies were examined in this study. Expression of a new acetyltransferase enzyme (EfDAcT) isolated from the seeds of Euonymus fortunei, which was previously shown to possess higher in vitro activity and in vivo acetyl-TAG levels compared to EaDAcT, increased acetyl-TAG accumulation by 20 mol%. Suppression of the endogenous competing enzyme DGAT1 further enhanced acetyl-TAG accumulation to 90 mol% in selected transgenic line. Studying the regulation of EfDAcT transcript, protein, and acetyl-TAG levels during seed development further provided new insights on the factors limiting acetyl-TAG accumulation.
Keywords: Acetyl-TAG; Euonymus fortunei diacylglycerol acetyltransferase; Camelina sativa; DGAT1-RNAi; Seed development